Daily Climate Extremes of Temperature and Precipitation Over Quetta Valley, Pakistan During 1961-2019 - Durrani, Imran Hameed; Adnan, Shahzada; Aftab, Syed Mobasher (International Journal of Environment, 2021)
Climate extremes are imperative to study the impacts of climate change that is significantly observed for the management of scarce water resources of the Quetta Valley. The daily data of temperature and precipitation are used to model the climate extreme indices for Quetta Meteorological Station from1961 to 2019. The statistical tests were performed by using Mann Kendal and Sen’s Slope method at the 95% confidence level. The overall change in minimum to maximum temperatures and precipitation-based climate extreme indices specify the frequencies of extreme events are increasing. That would cause heatwaves, gradual warming, steady dryness, and extreme precipitation events in the long term over the Quetta Valley. The minimum and maximum temperature-based indices inclusively indicate positive trends. That ultimately leads to a warming climate with a significant increase in summer as 5 days/decade, tropical nights as 5.3 days/decade, daily maximum as 0.28°C/decade, warm nights as 1.7 days/decade and warm days as 1.9 days/decade. For precipitation, all the indices show positive trends with a significant increase in consecutive wet days for 0.1 days/decade and an annual contribution of very wet days 0.8% per decade. The monthly increase in temperature and decrease in precipitation would increase the evaporative demands which may arise the water stress conditions over the valley and may put pressure over groundwater reservoirs.